2017
DOI: 10.1103/physrevb.95.125203
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced topological phase transition in the polar semiconductor BiTeBr

Abstract: We performed X-ray diffraction and electrical resistivity measurement up to pressures of 5 GPa and the first-principles calculations utilizing experimental structural parameters to investigate the pressure-induced topological phase transition in BiTeBr having a noncentrosymmetric layered structure (space group P 3m1). The P 3m1 structure remains stable up to pressures of 5 GPa; the ratio of lattice constants, c/a, has a minimum at pressures of 2.5 -3 GPa. In the same range, the temperature dependence of resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…Such pressure-induced electronic topological transitions constitute a common motif for layered materials and are evidenced by distinct compressibility and Raman intensity changes, without any alteration of the (average) crystalline symmetry. 58,[67][68][69] A thorough investigation of such a possibility, however, lies beyond the scope of the present paper.…”
Section: -4mentioning
confidence: 94%
“…Such pressure-induced electronic topological transitions constitute a common motif for layered materials and are evidenced by distinct compressibility and Raman intensity changes, without any alteration of the (average) crystalline symmetry. 58,[67][68][69] A thorough investigation of such a possibility, however, lies beyond the scope of the present paper.…”
Section: -4mentioning
confidence: 94%
“…Here, we would like to emphasize that a similar trend was reported in the pressure range 2.0  2.9 GPa and 2.5  3.0 GPa in BiTeI and BiTeBr, respectively and these changes were interpreted as the signature of TQPT. 9,10 To get more insight about c/a ratio anomalies, the pressure dependent Te(1)  Te(2) contact distance is plotted in Fig. S3.…”
Section: Figmentioning
confidence: 99%
“…18 Recently, Ohmura et al, showed that bismuth tellurihalide BiTeBr (S.G: P3m1, Eg = 0.55 eV) undergoes a TQPT at 2.5  3.0 GPa using resistivity and synchrotron XRD measurements under pressure. 10 The above examples provide strong basis for using such indirect methods to study pressure induced TQPT in the SOC systems.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations